Hidden in the dry woods: Mapping the collection history and distribution of Gymnanthes boticario, a well-collected but very recently described species restricted to the dry vegetation of South America - de Oliveira, Luciana Dos Santos D.; Moro, Marcelo Freire; Lughadha, Eimear M. Nic; Martins, Fernando Roberto; de Melo, André Laurênio; Esser, Hans-Joachim; Sales, Margareth F. (Phytotaxa, 2013)
Botanists estimate that 80 to 90% of existing plant species have already been described and it is expected that most undescribed species are rare or narrow endemic ones. Here we map the geographical distribution of Gymnanthes boticario, a species described in 2010, and show that the species is not only widespread, but was well-collected in the Caatinga semiarid vegetation prior to its description. During a revision of the genus Gymnanthes we also found collections of G. boticario in the Brazilian Mato Grosso do Sul state (in Pantanal ecoregion), in Paraguay (in Cerro Léon dry forests) and in Bolivia (in Chiquitano dry forest ecoregion) in a pattern that closely resembles the Pleistocenic Arc Hypothesis. We map the continental distribution of G. boticario, report the first records of it for Bolivia, Paraguay and the Brazilian Pantanal and show the rich data available in herbaria for a plant only recently described.